INDIVIDUAL DIFFERENCES IN SECOND LANGUAGE ACQUISITION - Ramlan Ginting Suka (Universitas Lampung, 2015)
This article presents the individual differences in learning and acquiring a second language. Some learners are successful in learning foreign language quickly while others feel frustrated. Gradman and Hanania (1991) state that there are 22 kinds of individual differences in learning foreign languages. This paper discusses five factors of individual differences. Each factor is expected to provide contribution in learning a second language. Furthermore, individual difference variables are expected to provide guidance to teachers to teach the second language effectively and efficiently.Key words: individual, differences, language acquisition